The Impact Of Rome I Regulatıon In Albanıan Prıvate Internatıonal Law - Mucmataj, Ilda (European Scientific Journal, ESJ, 2016)
In terms of globalization, the economic activities have overcome national boundaries of states. So due to people’s mobility and their frequent relations in private field, the number of private international actions has increased as well, and gives in this way the importance of private international law. The conflict of law rules in the national law were not unaffected by European integration. So, the developments that took place in the European Union in the field of private international law over the past years had a large impact on the national conflict of laws rules in Albania, especially on the conflict of laws rules of certain specific areas of law. The aim of this article is to analyze the interaction between European Union law and the Albanian conflict of laws rules in the area of contractual obligations. So on one hand, I have presented a general analysis on the main provisions of the EC Regulation No. 593/2008 of The European Parliament and of the Council of 17 June 2008 on the Law applicable to contractual obligations, known as (Rome I), as the role of the European Union is becoming increasingly active in PIL. While, on the other hand I have presented a short introduction of the historical development of APIL and its characteristics and then I have given a comparative view of Albanian Private international Law relating to the contractual obligations with the focus on party autonomy provisions. The article concludes with a short conclusion.